"SMART" BIOPLASTICS BASED ON FRUIT PEELS AND THEIR PROCESSING TECHNOLOGIES (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article discusses the possibilities of using local agricultural waste in the production of bioplastics, in particular, the technology for obtaining "smart" (with antibacterial properties) bioplastics based on fruit peels. The study analyzed the creation of a composite biopolymer based on starch, cellulose and natural extracts, its physicochemical properties, and environmental problems associated with polymer processing. As a result, the proposed material is characterized as an active packaging material that is not only biodegradable, but also extends the shelf life of food products.